2013
DOI: 10.1097/mat.0b013e3182a39628
|View full text |Cite
|
Sign up to set email alerts
|

Direct Thrombolytic Therapy for Thrombosis of a Centrifugal Flow Left Ventricular Assist Device

Abstract: In patients receiving left ventricular assistance for end-stage heart failure, pump-related thrombosis is a potentially fatal complication that may manifest as hemolysis and abnormally high pump power consumption. The optimal approach to treat this complication is unclear, especially in patients who are not heart transplant candidates or who have a high surgical risk. We report the successful use of direct thrombolytic therapy for recurrent hemolysis and thrombosis-related pump failure in a patient with the He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Four very similar case reports were published that all used similar strategies of intraventricular alteplase administration. All were successful, with similar dosing regimens of 1 mg/minute for varying times (20–37 min) until thrombus resolution, and pump parameter and hemodynamic improvements were directly observed . The patient from one of the case reports required two consecutive fibrinolytic sessions to achieve complete resolution of thrombus but was still managed successfully with this technique .…”
Section: Pharmacotherapy Of Device‐related Thrombosismentioning
confidence: 94%
“…Four very similar case reports were published that all used similar strategies of intraventricular alteplase administration. All were successful, with similar dosing regimens of 1 mg/minute for varying times (20–37 min) until thrombus resolution, and pump parameter and hemodynamic improvements were directly observed . The patient from one of the case reports required two consecutive fibrinolytic sessions to achieve complete resolution of thrombus but was still managed successfully with this technique .…”
Section: Pharmacotherapy Of Device‐related Thrombosismentioning
confidence: 94%
“…In clinical studies, almost no pump thrombosis was found inside these maglev ventricular assist pumps. 2225 Other than pump thrombosis, there were no significant differences between the HeartMate II axial blood pump and the Heartmate III maglev centrifugal pump with regard to the associated rates of other major complications, such as right heart failure, stroke, major infection, or gastrointestinal bleeding. 23 However, this lack of difference does not mean that there is no pump thrombosis in maglev pumps.…”
Section: Discussionmentioning
confidence: 98%
“…Several other studies reported on thrombolytic therapy of pump thrombosis. 7,[14][15][16] Schlendorf et al reported on eight patients who underwent intraventricular application of thrombolytics (1 mg/min over 30 min) with a 38% success rate. 16 The Evaluation of the HeartWare Left Ventricular Assist Device for the Treatment of Advanced Heart Failure (ADVANCE) trial reported on 31 patients with HVAD pump thrombosis.…”
Section: Discussionmentioning
confidence: 99%